Decline in cardiovascular mortality in North Karelia and other parts of Finland. Issue 6554 (25th October 1986) - Tuomilehto, J; Geboers, J; Salonen, J T; Nissinen, A; Kuulasmaa, K; Puska, P
Abstract : The trends in mortality from ischaemic heart disease, cerebrovascular stroke, and all cardiovascular diseases were analysed for the province of North Karelia and for the rest of Finland. Linear trends in mortality were computed for the population aged 35 to 64 for the period from 1969 to 1982, and changes in mortality between the three year means of 1969-71 and 1980-2 were calculated. In North Karelia, where a community based preventive programme has been carried out since 1972, the annual decline in mortality from ischaemic heart disease in men was on average 2.9%, whereas in the rest of Finland it was 2.0%. For women the respective average annual declines in mortality were 4.9% and 3.0%. The net decline from 1969-71 to 1980-2 in North Karelia was 100 deaths/100, 000 men. The annual mortality from all cardiovascular disease in men decreased by 2.9% in North Karelia and by 2.6% in the rest of Finland; in women the decreases were 6.0% and 5.0% a year, respectively. The net decline in North Karelia was 71 deaths/100, 000 men. The decline in mortality from all causes was also appreciable in both sexes in North Karelia, but it did not differ significantly from national trends.